IMPROVING OF ANTICORRUPTION BAN ON GIFTS, TAKING INTO ACCOUNT GERMAN EXPERIENCE - N. V. Khlonova (Russian Journal of Economics and Law)
The article views the problems arising during realization of a ban on taking gifts by state and municipal workers in Russia, in particular, the interpretation of the terms a usual gift, a gift connected with official position, the procedure of the gift evaluation and transferring it to the budget, as well as exceptions from the common ban. Taking into account the positive experience of Germany, the main directions of the gift ban improvement in Russia are suggested.